2010
DOI: 10.1002/ajpa.21250
|View full text |Cite
|
Sign up to set email alerts
|

Biocultural interpretations of trauma in two prehistoric Pacific Island populations from Papua New Guinea and the Solomon Islands

Abstract: Two Pacific Island skeletal samples originating from the inland site of Nebira, Papua New Guinea (1230-1650) and a coastal site on the small island of Taumako, Solomon Islands (1530-1698) were examined for evidence of skeletal trauma using a biocultural approach. The types of trauma identified were cranial trauma, postcranial fractures, and piercing and sharp force trauma. Both samples exhibit trauma (Nebira, n = 9/28, 32.1%; Taumako, n = 17/133, 12.8%). Postcranial fractures are significantly higher in males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 66 publications
2
29
0
1
Order By: Relevance
“…Six of the skeletons (five men and one woman) had healed cranial fractures consistent with sharp-force and blunt-force trauma. Scott and Buckley (2010) note that the level of trauma in the Nebira skeletal sample is relatively high compared with other skeletal studies of trauma worldwide and suggest that it may reflect tribal warfare in the area during the hilltop occupation of Nebira.…”
Section: The Archaeological Context Of Nebiramentioning
confidence: 92%
See 2 more Smart Citations
“…Six of the skeletons (five men and one woman) had healed cranial fractures consistent with sharp-force and blunt-force trauma. Scott and Buckley (2010) note that the level of trauma in the Nebira skeletal sample is relatively high compared with other skeletal studies of trauma worldwide and suggest that it may reflect tribal warfare in the area during the hilltop occupation of Nebira.…”
Section: The Archaeological Context Of Nebiramentioning
confidence: 92%
“…pressure in the area as a possible response to land warfare. Recent research on the skeletal evidence of trauma in the Nebira individuals by Scott and Buckley (2010) found that nine of the 28 sampled individuals from Nebira had evidence of skeletal trauma. Six of the skeletons (five men and one woman) had healed cranial fractures consistent with sharp-force and blunt-force trauma.…”
Section: The Archaeological Context Of Nebiramentioning
confidence: 98%
See 1 more Smart Citation
“…contribution of osteoporosis in increased frequency of fractures in postmenopausal females (Mensforth, Latimer 1989), reduced bone mass due to inactivity, poor health predisposition, geographic location (Kilgore et al 1997;Lovell 1997;Scott, Buckley 2010), or even the climate also play an important role in trauma etiology. the biocultural (Scott, Buckley 2010) and sociocultural context and historical records also need to be taken into consideration in the interpretation of traumatic events (lovell 1997).…”
Section: Discussionmentioning
confidence: 99%
“…As nowadays, injury has also played a significant role in past human societies, a role that can be accessed through a careful analysis of the skeletal remains [2]. Bone injury, resulting from interpersonal violence or associated with the hazards of daily life, is frequently reported in the paleopathological literature as a useful tool to decipher past behaviors and health conditions [3,4,5,6,7,8,9,10,11,12,13,14]. The prevalence and distribution of fractures constitute the marker most commonly investigated [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%